2020
DOI: 10.1097/dcr.0000000000001652
|View full text |Cite
|
Sign up to set email alerts
|

Readmissions Within 48 Hours of Discharge: Reasons, Risk Factors, and Potential Improvements

Abstract: BACKGROUND: Hospital readmission rate is an important quality metric and has been recognized as a key measure of hospital value-based purchasing programs.OBJECTIVE: This study aimed to assess the risk factors for hospital readmission with a focus on potentially preventable early readmissions within 48 hours of discharge.DESIGN: This is a retrospective cohort study. SETTINGS:This study was conducted at a tertiary academic facility with a standardized enhanced recovery pathway.PATIENTS: Consecutive patients unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…HOS-related complications together with postoperative ileus/obstruction and deep infections are seen as the main reasons for readmission after elective colorectal surgery. 3 The results of our study confirm that morbidity related to the first factor is significant, with HOS-related readmission in three patients (4%) and need for intensive care unit admission in one of them within 1 week after discharge. Additionally, 9 patients (11%) experienced a delay in discharge during elective admission because of HOS which is a known risk factor for readmission.…”
Section: Discussionsupporting
confidence: 78%
“…HOS-related complications together with postoperative ileus/obstruction and deep infections are seen as the main reasons for readmission after elective colorectal surgery. 3 The results of our study confirm that morbidity related to the first factor is significant, with HOS-related readmission in three patients (4%) and need for intensive care unit admission in one of them within 1 week after discharge. Additionally, 9 patients (11%) experienced a delay in discharge during elective admission because of HOS which is a known risk factor for readmission.…”
Section: Discussionsupporting
confidence: 78%
“…The primary outcome was the correlation between cumulative fluid balance (ml) and daily weight (kg) variations. More specifically, weight at POD 2 (previously identified as most predictive cutoff to launch potential counter-regulatory measures) was correlated with fluid balance at POD 1 (most accurately representing perioperative fluid balance) [28][29][30].…”
Section: Outcomes/study Endpointsmentioning
confidence: 97%
“…Hospital readmission is considered a quality metric for hospital value-based purchasing programs. 20 This study demonstrates that interventions designed to target common reasons for readmissions significantly decreased enhanced recovery colorectal surgery readmission rates from 17.82% to 9.98% and ED visits from 23.15% to 14.58%. There was a significant decrease in readmissions due to SSI I/II infections.…”
Section: Discussionmentioning
confidence: 64%
“…A retrospective cohort study showed that 25% of readmissions occur within 48 hours of discharge and are often due to ileus, whereas readmissions >48 hours after discharge are related to deep SSIs and AKI. 20 Our median time to readmission after discharge was 6 (IQR 3–11) days in the preintervention group and 8 (IQR 3–17) days in the postintervention group. Median time for readmission after discharge (preintervention vs postintervention) for ileus in our study was 2.5 days vs 3 days, and for AKI/dehydration was 7 days vs 15 days.…”
Section: Discussionmentioning
confidence: 76%